PENYANDANG DISABILITAS DAN UU NOMOR 11 TAHUN 2020 TENTANG CIPTA KERJA - Bintang Kharisma; Sofyantoro Sofyantoro (Keadilan : Jurnal Fakultas Hukum Universitas Tulang Bawang, 2020)
Persons with disabilities constitute the highest minority group in the world. This number is expected to continue to increase from year to year in line with world population growth, natural disasters and other factors. The purpose of this study is to determine the relationship related to work creation which is not friendly to people with disabilities. The research method used is literature study with the main source, namely the law number 11 of 2020 concerning Job Creation. The result of this research is that the Job Creation Law does not actually support the fulfillment of the rights of persons with disabilities in getting proper accommodation in the world of work. The Job Creation Law does not include a 1% quota provision for private companies and 2% for BUMN / BUMD and Government / Local Government to employ persons with disabilities from all employees, which are currently listed in the Law on Persons with Disabilities.